Fatigue Detection (DTIK) : Monitoring a Fatigue - Rumentalia Sulistini; Devi Mediarti; Imelda Erman; Ririn Sri Handayani (Jurnal Keperawatan Silampari, 2023)
This study aims to develop an application to detect fatigue and educate people about diabetes. The research method used is Research and Development (R&D). The analysis results obtained the conformity of the validation results of media experts 1 and 2 (kappa 0.654; p = 0.001). 95.5% of people with diabetes stated that the application was feasible without revision. The application contains a menu of measurement and education. In conclusion, DTIK is an application that can detect fatigue more efficiently during the COVID-19 pandemic. This application is free and can be used by people with diabetes anywhere and anytime. Keywords: Application, Fatigue Detection, Diabetes Education